Pinnipeds and PTSD: An Analysis of a Human-Animal Interaction Case Study Program for a Veteran - Rachel A. Wortman; Theresa Vallone; Michele Karnes; Christine Walawander; Dion Daly; Bonnie Fox-Garrity (Occupational Therapy International)
The objective of this study was to examine the impact of a pinniped (grey and harbor seals) facilitated human-animal interaction pilot program on the self-reported PTSD-like symptoms of a veteran. This study analyzed preexisting, deidentified data that represented the participant’s scores on the Post-Traumatic Stress Disorder Checklist (PCL-5). The PCL-5 was completed as part of a pilot program operated in partnership between the Veteran and Military Affiliated Research Center (VMARC) and a local aquarium. Scores on the PCL-5 were collected prior to (T1), midway (T2), and immediately after (T3) completion of the Project Seal to Heal program. Changes in the scores of each item were reported for the participant, for aggregated items that represented different clusters of PTSD symptoms, and for overall scores. Results revealed decreased scores in 11 of the 20 PTSD symptom-related items, improvement in the sum scores for each criteria symptom cluster, and a 15-point decrease in the overall PCL-5 score, indicating clinical significance. These results serve as a call to motivate future research investigating pinniped interactions with veterans who have PTSD in order to determine therapeutic clinical application and outcomes.